Intra-Arterial Treatment Methods in Acute Stroke Therapy - Nguyen, Thanh; Babikian, Viken; Romero, Rafael; Pikula, Aleksandra; Kase, Carlos; Jovin, Tudor G.; Norbash, Alexander M. (Frontiers in Neurology, 2011)
Acute revascularization is associated with improved outcomes in ischemic stroke patients. It is unclear which method of intra-arterial intervention, if any, is ideal. Promising approaches in acute stroke treatment are likely a combination of intravenous and endovascular revascularization efforts, combining early treatment initiation with direct clot manipulation and/or PTA/stenting. In this review, we will discuss available thrombolytic therapies and endovascular recanalization techniques, beginning with chemical thrombolytic agents, followed by mechanical devices, and a review of ongoing trials. Further randomized studies comparing medical therapy, intravenous and endovascular treatments are essential, and their implementation will require the wide support and enthusiasm from the neurologic, neuroradiologic and neurosurgical stroke communities.